PP28 The incidence and cause of perinatal mortality and severe maternal morbidity in Ireland: findings from two national clinical audits. (2nd September 2014) - Corcoran, P; Manning, E; Meaney, S; Lutomski, JE; O'Connor, L; Drummond, L; Greene, RA
Abstract : Background: In high-resource countries where maternal mortality is very rare, perinatal mortality and severe maternal mortality have become markers for the quality of care in maternity services. As two of the most adverse pregnancy outcomes, there is a need for in-depth clinical audit of perinatal mortality and severe maternal morbidity in order to understand the causes, to guide clinical practice and to improve prevention. Methods: Under the guidance of two national groups, we developed the audit methodologies from those of the UK Centre for Maternal and Child Enquiries Perinatal Mortality Audit and the Scottish Confidential Audit of Severe Maternal Morbidity. Severe maternal morbidity was defined as experience of major obstetric haemorrhage, eclampsia, renal/liver dysfunction, cardiac arrest, pulmonary oedema, acute respiratory dysfunction, coma, cerebrovascular accident, status epilepticus, septicaemic shock, anaesthetic complications, pulmonary embolism, peripartum hysterectomy, Intensive Care Unit (ICU) admission or interventional radiology. Both audits were implemented in 2011 with all 20 Irish maternity units providing anonymised data on cases of perinatal death and severe maternal morbidity via paper notification form or custom-designed online data entry system. Results: For 2011, 491 perinatal deaths were reported, 318 (65%) stillbirths, 138 (28%) early neonatal deaths and 35 (7%) late neonatal deaths, giving a perinatal mortality rate of 6.1/1000 births (95% CI=5.6–6.7/1000), stillbirth rate of 4.3/1000 births (95% CI=3.8–4.8/1000) and early neonatal death rate of 1.9/1000 live births (95% CI=1.5–2.2/1000). Fourfold variation in the perinatal mortality rate was observed across the 20 maternity units. The common causes of death in stillbirth were congenital anomaly (26%), placental conditions (17%) and ante/intrapartum haemorrhage (11%), 20% were unexplained. Early neonatal deaths were generally due to congenital anomaly (51%) or respiratory disorder (33%) - primarily severe pulmonary immaturity. Just 4% were unexplained. Low birthweight was common, below normal range for 53% of stillbirths and 40% of early neonatal deaths. In 2011, 260 women experienced severe maternal morbidity, a national rate of 3.8/1000 maternities (95% CI=3.4–4.3/1000). Almost half (42.3%) experienced two or more severe morbidities. Major obstetric haemorrhage was the most frequent morbidity (61.2%, 2.3/1000 maternities) followed by ICU admission (42.7%, 1.6/1000 maternities), renal/liver dysfunction (10.0%, 0.4/1000 maternities) and peripartum hysterectomy (8.8%, 0.3/1000 maternities). Major obstetric haemorrhage was associated with Caesarean section and peripartum hysterectomy was associated with a history of Caesarean section and a morbidly adherent placenta. Conclusion: While limited international comparisons can be made, the incidence of perinatal mortality and severe maternal morbidity in Ireland compares favourably to other European countries.